1977
DOI: 10.1111/j.1748-5827.1977.tb05820.x
|View full text |Cite
|
Sign up to set email alerts
|

The bacterial flora of the normal canine vagina compared with that of vaginal exudates

Abstract: The aerobic bacterial flora (excluding Mycoplasma spp.) of the vagina of sixty‐two clinically normal bitches was determined and the species most frequently isolated, in decreasing order, were: Escherichia colt, Streptococcus ‘viridans’, Staphylococcus aureus and Streptococcus cards. From the vaginal exudates of seventy‐two bitches with vaginitis, the order of frequency was: E. coli, Strep, canis and Staph. aureus. The only consistent difference between the bacterial flora from the two sources was the relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 0 publications
3
14
1
Order By: Relevance
“…The species of bacteria in the uterus, cervix and vagina of the bitch during pro-oestrus and oestrus were similar to those previously isolated from the vagina (Hirsh and Wiger 1977, Baba and others 1983, Olson and others 1986, Bjurstrom and Linde-Forsberg 1992. Haemophilus species has been suggested as a cause of vaginitis (Osbaldiston 1971) but was not associated with any reproductive tract disease in our study.…”
Section: Discussionsupporting
confidence: 81%
“…The species of bacteria in the uterus, cervix and vagina of the bitch during pro-oestrus and oestrus were similar to those previously isolated from the vagina (Hirsh and Wiger 1977, Baba and others 1983, Olson and others 1986, Bjurstrom and Linde-Forsberg 1992. Haemophilus species has been suggested as a cause of vaginitis (Osbaldiston 1971) but was not associated with any reproductive tract disease in our study.…”
Section: Discussionsupporting
confidence: 81%
“…), information on sources of bacteria in newborn dogs is still limited. E. coli is part of the normal intestinal flora in dogs and can also be isolated from the vagina in healthy female animals (Hirsh and Wieger ; Olson and Mather ; van Duijkeren ). Vaginal discharge (Bjurström ), faecal bacteria, bacteria of the oral cavity (Münnich and Lübke‐Becker ) and the contaminated environment are potential sources of infections in young dogs, similar to the situation in humans (Saizou et al.…”
Section: Infectious Diseases – Bacterial Infectionsmentioning
confidence: 99%
“…and Moraxella spp. [8][9][10]14,15,[17][18][19][20][21][22][23][24][25][26]. Some of these bacteria are isolated from both fertile and infertile dogs [2] with similar types of aerobes as part of the vaginal microflora of both groups of animals [11].…”
Section: Resultsmentioning
confidence: 99%
“…Different investigations have shown that microorganisms into the vagina of clinically healthy bitches are isolated also from patients with genital system inflammation [13,17]. The most common are E. coli, Staphylococcus spp., Streptococcus spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation